Sweden : 2002 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Sweden. (IMF Staff Country Reports; Country Report, 2002)
This 2002 Article IV Consultation highlights that a cyclical slowdown in domestic demand coupled with global economic weakness led to slower growth of Sweden in 2001. Private consumption stagnated despite rising disposable income, owing to adverse confidence and wealth effects from the continued plunge in stock prices. Exports suffered their weakest year in a quarter century, as telecom exports-the driving force behind the recent rapid growth-fell by about one-third. The weak krona and supportive fiscal and monetary policies, however, helped contain the severity of the slowdown.